Seismic Evidence for Stepwise Lithospheric Delamination Beneath the Tibetan Plateau. Issue 10 (12th May 2022) - Wu, Yingkai; Bao, Xuewei; Zhang, Bingfeng; Xu, Yixian; Yang, Wencai
Abstract: Several models were proposed to account for the tectonic evolution of Tibetan Plateau, among which delamination of the Tibetan lithosphere is suggested to be a leading process. However, direct evidence for the removed Tibetan lithosphere in the deep mantle remains highly lacking. Here we image the mantle transition zone (MTZ) structure beneath western Tibet and Himalaya by common conversion point stacking of 25254 receiver functions (RFs) with unprecedented clarity. One striking feature is the significant depression (15–20 km) of 660‐km discontinuity beneath Himalaya, which indicates the presence of the detached Lhasa lithospheric mantle (∼26 Ma) at the bottom of the MTZ. Our results also show ∼15 km uplift of 410‐km discontinuity (d410) and small d410 amplitude beneath western Tibet, which we ascribe to the more recently delaminated Qiangtang lithosphere (∼15 Ma). Furthermore, the small dependence of d410 amplitude on frequency indicates that the MTZ is anhydrous in the study area. Plain Language Summary: The fate of the original Tibetan lithosphere during the continental collision and its role in the tectonic evolution of the plateau remain highly debated. Here we image the mantle transition zone bounded by 410‐km (d410) and 660‐km (d660) discontinuities beneath western Tibet and Himalaya, suggesting the stepwise delamination of the Tibetan lithosphere. Our results show the significantly depressed d660 beneath the Himalaya terrane, which we interpret as reflecting the delaminated Lhasa lithosphere (∼26 Ma) stagnant near the d660. Our image also reveals prominent uplift and small amplitude of d410 beneath western Tibet, indicating the presence of delaminated Qiangtang lithosphere (∼15 Ma) in the vicinity of d410. The MTZ in the study region is anhydrous through multifrequency analysis of receiver functions, which shows small variations in d410 amplitude in all the frequency bands considered here. Key Points: Detailed structure of the mantle transition zone (MTZ) beneath western Tibet and Himalaya suggests stepwise delamination of Tibetan lithosphere The depressed 660‐km discontinuity beneath Himalaya is due to the delaminated Lhasa lithosphere (∼26 Ma) stagnant at the bottom of the MTZ The uplifted 410‐km discontinuity beneath western Tibet is caused by the delaminated Qiangtang lithosphere (∼15 Ma)